Building external anatomical structures from images using a single off-the-shelf camera - Teresa Cristina de Sousa Azevedo (2007)
Three-dimensional (3D) geometric reconstruction and characterization of the human body from bidimensional (2D) images has been a major research topic in Computer Vision. However, it is still a complex problem to solve, when automation, speed and precision are required. Volumetric based methods are a recent and successful solution for 3D structures reconstruction from images. In this work, using an uncalibrated turntable image sequence, acquired with a single off-the-shelf CCD camera, a 3D geometric model of the structure in cause is built. Our main goal is the reconstruction of 3D shapes of external anatomical structures from images, with good precision and photorealistic appearance.